Revisiting Hadith Through Philology: Ignaz Goldziher's Skeptical Arguments and the Reactualization of Hadith Criticism Methodology - Nur Amaliyah; Sholahuddin Al Ayubi; Muhamad Afif (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study addresses the methodological gap between Western philological skepticism exemplified by Ignaz Goldziher’s critique of hadith authenticity and the classical Islamic critical apparatus of jarh wa ta’dil. Despite decades of scholarly debate, no integrative methodological framework has been explicitly operationalized to bridge these two traditions. Design/Methodology/Approach: Using a qualitative-library method, this research systematically selects and analyzes primary sources (Goldziher’s Muhammadan Studies; al-A’zami, Fazlur Rahman, and Ali Mustafa Yakub’s counter-arguments) alongside recent Scopus/WoS-indexed secondary literature. Data analysis employs a philological-critical and hermeneutical approach, validated through source triangulation. Findings: Three specific findings emerge: (1) Goldziher’s philological method raises legitimate socio-historical questions but systematically underestimates the rigor of isnad verification; (2) Muslim scholarly responses evolved from apologetic refutation to methodologically enriched engagement; (3) an Integrative Hadith Criticism Framework (IHCF) combining philological matan analysis with classical sanad verification is both theoretically viable and academically productive. Originality/Value: The novelty lies in proposing an operationalized Integrative Hadith Criticism Framework (IHCF) that transcends the apologetic-versus-skeptical binary and provides a concrete cross-disciplinary methodology applicable to contemporary digital humanities contexts in hadith studies. The implication is that the methodology of hadith criticism can be proactively renewed remaining critically rigorous while preserving the normative authority of hadith as a living source of Islamic law and praxis.